2000
DOI: 10.1111/1468-2370.00034
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement in industrial R&D

Abstract: Currently, the need for R&D performance measurements that are both practically useful and theoretically sound seems to be generally acknowledged; indeed, the rising cost of R&D, greater emphasis on value management and a trend towards decentralization are escalating the need for ways of evaluating the contribution of R&D to corporate performance. However, although recent research and writing on the subject shows that the challenge of developing such sound measurements has been taken up by many academics and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 74 publications
(142 reference statements)
3
61
0
1
Order By: Relevance
“…In this context, PM on R&D helps to creates links between the organisation's strategy and R&D by translating the organisation's strategy into performance measures which could, in turn, be linked to R&D activities. A number of studies have revealed that PM of R&D plays a vital role by influencing and helping organisations to implement their strategies (Bremser and Barsky, 2004;Pearson et al, 2000;Kerssens-van Drongelen et al, 2000;Kerssens-van Drongelen and Bilderbeek, 1999;Werner and Souder, 1997;Brown and Svenson, 1988). Yawson et al (2006) argue that PM for R&D activities provide the basis to assess whether the organisation is progressing towards its goals, identifies the strengths and weaknesses, decides on the future actions needed for improvements and provides data to request additional resources hence facilitating the implementation strategies.…”
Section: Value Of Performance Measurement For Research and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, PM on R&D helps to creates links between the organisation's strategy and R&D by translating the organisation's strategy into performance measures which could, in turn, be linked to R&D activities. A number of studies have revealed that PM of R&D plays a vital role by influencing and helping organisations to implement their strategies (Bremser and Barsky, 2004;Pearson et al, 2000;Kerssens-van Drongelen et al, 2000;Kerssens-van Drongelen and Bilderbeek, 1999;Werner and Souder, 1997;Brown and Svenson, 1988). Yawson et al (2006) argue that PM for R&D activities provide the basis to assess whether the organisation is progressing towards its goals, identifies the strengths and weaknesses, decides on the future actions needed for improvements and provides data to request additional resources hence facilitating the implementation strategies.…”
Section: Value Of Performance Measurement For Research and Developmentmentioning
confidence: 99%
“…Seaden and Mnseau (2001) and Hodkinson (1999) asserted that due to improper reporting mechanisms, the parties involved within R&D projects do not have a clear understanding of its status thus, the importance of creating clear and visible links between the R&D spending and their impact was highlighted. Kerssens-van Drongelen et al (2000) indicated that the accountability of R&D investments has increased due to the interest of investors and shareholders on knowing the utilisation of R&D resources. Therefore, as discussed above, PM would improve the reporting structure of R&D projects and would show how R&D investment is used hence, enhancing the success of R&D activities.…”
Section: Positive Impacts Of Performance Measurementmentioning
confidence: 99%
“…At the same time, the research and development phase is expanding (Back-Hock, 1992). The competitive advantage lies in resources that are not easily measured by traditional financial metrics, such as ongoing research and development (Brown -Svenson, 1998;Kerssens-van Drongelen et al, 2000;Pearson, 2010;Bremser, 2004). Therefore, R&D managers face challenges when making long-term R&D plans (Tierlinck, 2013).…”
Section: Literary Reviewmentioning
confidence: 99%
“…In a way, auto enterprises' synergistic innovation is a process in which innovation resources ( RE ) is integrated, and in which various kinds of resources carriers urge innovation resources to serve synergistic innovation of multi-institution, of multi-department and of multi-areas in terms of co-building R&D institutions, constructing R&D virtual network [5] , cultivating R&D sharing platform and changing the ownership attribute of R&D resources. Auto enterprises' synergistic innovation needs extensive recourses, including not only such tangible innovation resources as R&D expense input (RE1), R&D equipment, software and laboratories (RE2), but intangible ones like schools, scientific research institutions [6] , suppliers ( RE3 ) and leaders' attention ( RE4 ) .…”
Section: A Auto Enterprises' Synergistic Innovation and Resourcesmentioning
confidence: 99%